2021
DOI: 10.17951/sil.2021.30.2.357-379
|View full text |Cite
|
Sign up to set email alerts
|

Świadomość ekologiczna społeczeństwa polskiego w zakresie zasobów naturalnych i ich ochrony (przegląd badań)

Abstract: <p>The article comprises an analysis of public opinion surveys concerning the environmental awareness in Polish society concerning natural resources and their protection, which issue has not been presented to date comprehensively in the literature on the subject. To this end, i.e. to present the degree of this awareness, the results of opinion surveys on the following topics have been presented and analysed: environmental protection as a social problem and the sources of knowledge on this subject, climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Our research shows that although the majority of respondents agree with the statement that the slowdown in the economy due to the pandemic has contributed to the improvement of the environment, almost 1/3 of respondents could not clearly comment on this issue. We think that this is largely related to the general level of environmental awareness of Polish residents, which Stefaniuk [52] says, and which was confirmed, is not optimal but is gradually increasing.…”
Section: Discussionmentioning
confidence: 84%
“…Our research shows that although the majority of respondents agree with the statement that the slowdown in the economy due to the pandemic has contributed to the improvement of the environment, almost 1/3 of respondents could not clearly comment on this issue. We think that this is largely related to the general level of environmental awareness of Polish residents, which Stefaniuk [52] says, and which was confirmed, is not optimal but is gradually increasing.…”
Section: Discussionmentioning
confidence: 84%
“…Also, a survey of students at Podlasie Universities found that despite not having extensive environmental knowledge, they are characterized by high environmental awareness (Moroz et al, 2021). Moreover, environmental protection is increasingly perceived by consumers as one of the most important problems facing Poland (Stefaniuk, 2021). A special role in the pursuit of sustainable development has been attributed to cities for years (Popova, Zagulova, 2022), so one of the important manifestations of consumers' green attitudes is their decisions related to the form of urban transportation.…”
Section: Resultsmentioning
confidence: 99%
“…Podsumowując, aborcja ze względów społecznych była w Polsce dopuszczalna w latach 1956-1993 oraz w 1997 r. W 1993 r. wprowadzono w życie tzw. "kompromis aborcyjny", który pozwalał na przerwanie ciąży w trzech przypadkach: gdy ciąża stanowiła zagrożenie dla zdrowia lub życia kobiety ciężarnej, w sytuacji upośledzenia płodu oraz w sytuacji przestępnego pochodzenia ciąży 32 . Od 27.01.2021 r. dokonanie legalnej aborcji nie jest możliwe w przypadku wad płodu -opisywane wyżej orzeczenie TK doprowadziło do wyeliminowania przesłanki embriopatologicznej jako podstawy do terminacji ciąży.…”
Section: Polskie Prawo Aborcyjne Z Perspektywy Historycznejunclassified